PENGEMBANGAN MODUL PEMBELAJARAN INTERAKTIF BERBASIS APLIKASI KODULAR PADA MATA PELAJARAN BISNIS RITEL DI SMK NEGERI 6 JAKARTA - Desti Hapsari; Annisa Lutfia; Kusworo (STKIP Subang, 2026)
This study aims to develop and analyze the feasibility of an interactive, Kodular-based learning module for the retail business course at SMK Negeri 6 Jakarta. This study used the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The module was developed with elements of product packaging and distribution in the retail business course. The research subjects were students in Grade XI Retail Business I and Grade XI Retail Business II at SMK Negeri 6 Jakarta. The results of the study on the interactive learning module based on the Kodular application indicated a “highly feasible” category, consisting of a 96% score from the media expert review, a 94% score from the content expert review, an 83% score from the instructional design expert review, and a 92% score from the student pilot test. Meanwhile, the results of the effectiveness test using the N-Gain method yielded an average score of 0.7, classified as “moderate.” These results indicate that using the module improved students’ learning outcomes compared to before its implementation. Thus, based on the evaluation results, the interactive learning module based on the Kodular application for the retail business course at SMK Negeri 6 Jakarta is deemed highly suitable and effective for use as a learning medium. This can assist students and teachers in independent learning activities.